Reformar el art.797 del código de procedimiento civil, en cuanto a los alcances jurídicos de la declaratoria de utilidad pública de carácter urgente y de expropiación inmediata - Noriega Polo, Enrique Benjamìn (2014)
Our Constitution in its article 30, mentions that "the property in any of its forms and as long as it meets its social function, is a right which the State recognizes and guarantees for the Organization of the economy." You must ensure the increase and the redistribution of income, and allowing the population access to the benefits of wealth and development. It will recognize and ensure intellectual property, under the terms laid down in the law and in accordance with the conventions and treaties in force". That is to say, the Constitution conceives of the property as a "civil right", from the level of the individual, and is a means to achieve the full development of the moral and material of the person. At the same time refers to the "expropriation" which is depriving a person of the ownership of an asset or a right, giving to change compensation. Done for reasons of public utility or social interest referred to in laws because we realize that for public institutions is beneficial for expropriated persons cause them harm both social and economic. The compulsory purchase, is a measured Comptroller of the Administration that depriving the managed private ownership of certain assets, rights or interests of a patrimonial nature, in Exchange for compensation, called fair price. Although according to the law to be mutual agreement mostly discourages to the expropriated, causing serious consequences both social and economic. Under that the object of this project is to analyze specifically the procedure for the acquisition of real estate by declaration of public utility or social interest in the autonomous governments of the country, generally will be referred to the expropriation power which is contemplated in the organic code of Territorial Planning, autonomy and decentralization.